Answer:
44 = b
Explanation:
The equation for a circle centered in the point (a, b) and of radius R is:
(x - a)^2 + (y - b)^2 = R^2
Now we start with the equation:
x^2 + y^2 - 4x + 2y = b
First, we can reorder the terms as:
(x^2 + 2*(-2)*x) + (y^2 + 2*y) = b
Now let's complete the squares:
In the first parentheses we can add and subtract 4
(x^2 + 2*(-2)*x + 4 - 4) + (y^2 + 2*y) = b
(x^2 - 2)^2 - 4 + (y^2 + 2*y) = b
Now let's complete the other square, here we need to add and subtract 1.
(x^2 - 2)^2 - 4 + (y^2 + 2*y + 1 - 1) = b
(x^2 - 2)^2 - 4 + (y + 1)^2 - 1 = b
(x^2 - 2)^2 + (y + 1)^2 = b + 1 + 4
Then the radius of this circle is:
R = √(b + 1 + 4)
And we know that R = 7, then:
7 = √(b + 1 + 4)
7^2 = b + 1 + 4
49 = b +5
49 - 5 = b
44 = b